Changing Public Perceptions and Supporting Improved Working Conditions for the Social Service Workforce: Expert Perspectives from a Global Delphi Study. Issue 47 (2nd November 2021) - Akesson, Bree; Milne, Lise; Canavera, Mark; Meyer, Elizabeth; Reinke, Christina
Abstract: The scholarship has yet to investigate the multifaceted ways that working conditions and public perception both play a fundamental role in fostering a healthy and effective social service workforce. This paper describes a global study to develop consensus on ideal practices and approaches to strengthen the social service workforce. Using a mixed methods Delphi technique, 43 experts across a range of social service practice and geographical settings answered the research question: What are effective practices and approaches to strengthening the social service workforce? Data were used to inductively create two themes: (a) public perception, recognition, and political will; and (b) working conditions. Participants agreed that working conditions that foster health and resilience for workers must ensure not only appropriate remuneration and work environment but also conditions that facilitate motivation. The findings emphasize that improving working conditions is highly dependent upon elevating public understanding and perceptions of the profession across the globe. The paper ends with a call for future research to collect richer and more in-depth data on the topic, to gather information from social service workers from diverse backgrounds, and to more closely examine the relationship between the media, public perception, and the gendered nature of social service work.